Evaluation Report on Working of Community Projects and N.E.S. Blocks PEO PC 1956 - Planning Commission (Planning Commission, 1956)
The community development programme is now in its fourth year. The first 55 community projects which stirred the imagination of the country are now in their closing stages. The intervening years have seen the transformation of the programme from an experiment initiated in a few areas to a nation-wide programme of rural development. The pattern of the national extension service has been accepted as the basic pattern of rural development administration in the welfare State and it is proposed to extend it over the whole country during the Second Plan period. Besides, a very large area will receive the intensive development effort under the community project phase.
Planning Commission Programme Evaluation Organisation